2007
DOI: 10.1007/s00221-007-1237-0
|View full text |Cite
|
Sign up to set email alerts
|

Walking performance and its recovery in chronic stroke in relation to extent of lesion overlap with the descending motor tract

Abstract: We investigated the association between the degree of lesion overlap with the corticospinal tract and walking performance before and after 4-weeks of partial body weight support (PBWS) treadmill training in 18 individuals (ten male, eight female) with a mean age 59 +/- 13 years (mean +/- SD), range 32-74 years, who were ambulant and 6 months from a subcortical ischaemic stroke. Lesion volumes were manually defined on high resolution T1-weighted 3T-MRI scans and a probabilistic map of the corticospinal tract cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 46 publications
7
62
2
3
Order By: Relevance
“…Past studies have suggested that residual corticospinal cord integrity is a predictor for recovery of upper limb function (Stinear et al 2007;Tombari et al 2004). In the present study, residual corticospinal integrity was not significantly correlated both to functional improvements and to changes in MEP size, which is in support of such studies targeting lower limb muscles (Dawes et al 2008). Lower limb muscles have been suggested to be under less cortical control compared with upper limb muscles (Peters 1990).…”
Section: Discussionsupporting
confidence: 74%
“…Past studies have suggested that residual corticospinal cord integrity is a predictor for recovery of upper limb function (Stinear et al 2007;Tombari et al 2004). In the present study, residual corticospinal integrity was not significantly correlated both to functional improvements and to changes in MEP size, which is in support of such studies targeting lower limb muscles (Dawes et al 2008). Lower limb muscles have been suggested to be under less cortical control compared with upper limb muscles (Peters 1990).…”
Section: Discussionsupporting
confidence: 74%
“…28 Patients had to score Ն3 on the Functional Ambulatory Capacity rating scale. 29 Residual gait impairment had also to be confirmed by an abnormal 10-m walk time with age-adjusted thresholds.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…20 We wanted to investigate functional reorganization subsequent to treadmill training 24 in patients with stroke with gait impairment using fMRI and a paradigm involving more distal active and passive lower limb movements (ie, ankle dorsiflexion). 22 Accounts of the cross-sectional fMRI findings from this cohort at baseline 27 and of the behavioral training data 28 already have been reported. Only patients with subcortical ischemic lesions that did not affect the cortex were included.…”
mentioning
confidence: 96%
“…These intuitive findings are in line with previous studies mapping corticospinal tract lesions to motor impairment and motor function recovery in patients with ischemic stroke. [23][24][25][26][27] Using a similar methodological approach, Lo et al 10 identified areas in the corona radiata critical for motor function recovery measured by the Arm Motor Ability Test. The mRS broadly assesses the degree of disability or dependence in the daily activities, which strongly depend on intact motor functions.…”
Section: June 2014mentioning
confidence: 99%